Richards equation for the assessment of landslide hazards - Ramesh Chandra Timsina (Bibechana)
In this work, we study the numerical simulation models for water ow in variably saturated (unsaturated) soils. These models are fundamental tools for the problems in soil related disciplines and water related risks analysis. In recent years, it is requisite to study the water resource management system and soil water related disasters and agricultural with global environmental eect. Numerous simulation models are widely used for modeling of water ow in porous media especially in unsaturated soils, among them Richards equation is the most important model. It is a highly nonlinear parabolic PDE with rare analytic solutions adopting particular cases occurring less accuracy. Therefore a novel and robust numerical approximation is essential for the simulation of the model. We introduce a numerical procedure by linearizing the model equation with the help of Kirchho integral transformation and discretize with dierent time stepping schemes. We interconnect the solution of the equation for the assessment of the landslide hazards. A hydrological model of innite slope stability is adopted to the solution of axi symmetrical form of Richards equation to nd the factor of safety, which helps to locate the potential landslide area in geological surface. Also, prediction of landslide can be made depending on the physical, geological, and topographical structure of the landscape.